Time-Depth Curve Evaluation Method for Conversion Time to Depth at Penobscot Field, Nova-Scotia, Canada - Fitri Rizqi Azizah; Puguh Hiskiawan; Sri Hartanto (Jurnal ILMU DASAR, 2016)
Oil and natural gas as a fossil fuel that is essential for human civilization, and included in nonrenewable energy, making this energy source is not easy for updated availability. So that it is necessary for exploration and exploitation reliable implementation. Seismic exploration becomes the method most widely applied in the oil, in particular reflection seismic exploration. Data wells (depth domain) and seismic data (time domain) of reflection seismic survey provides information wellbore within the timescale. As for the good interpretation needed information about the state of the earth and is able to accurately describe the actual situation (scale depth). Conversion time domain into the depth domain into things that need to be done in generating qualified exploration map. Method of time-depth curve to be the method most preferred by the geophysical interpreter, in addition to a fairly short turnaround times, also do not require a large budget. Through data information check-shot consisting of the well data and seismic data, which is then exchanged plotted, forming a curve time-depth curve, has been able to produce a map domain depth fairly reliable based on the validation value obtained in the range of 54 - 176m difference compared to the time domain maps previously generated.Keywords: Energy nonrenewable, survei seismik, peta domain waktu, peta domain kedalaman, time-depth curve